Goat production systems in Punjab, Pakistan - Muhammad, M.S.; Abdullah, M.; Javed, K.; Khan, M.S.; Jabbar, M.A. (2015)
The present study was conducted to explore the rural goat production system and know the involvement of rural families in this enterprise by using household surveys. The survey was conducted in six villages at two experimental sites (Bahawalpur and Faisalabad). Fifty five households from each village were interviewed using stratified random sampling method. Information about livestock inventory, production of goat, type of production systems and parameters, management of goat, and breeding strategies were recorded. Household heads were the incharge of farm activities at both sites in most of the cases (91.40% vs 91.97%). Interests in goat keeping were similar at both sites (83.11% & 80.15%). Flock sizes averaged 7.14 and 4.87 at both sites, respectively. Majority of the farmers kept goats mainly for home consumption (23.03% and 17.93% at Sites I and II, respectively). Main production system adopted in the spring (58.5% and 55.4%), summer (52.9% & 51.2%), rainy (57.7% & 52.9%) and winter (60.2% & 56.3%) seasons were intensive and semi-intensive at Sites I and II, respectively. Types of housing during day time were free range (47.9% & 35.3%) and during night confinement in sheds (87.0% & 72.9%) at Sites I and II, respectively. Most of the farmers' time was spent on marketing goats at Sites I and II (1.15 vs 1.95 Hrs), respectively. Main feeding regime was grazing and more farmers used grazing at Site-I (45.45%) as compared to Site-II (5.80%) while feed ingredients were used by the majority of farmers at Site-II (26.81%) as compared to Site-I (14.94%). Twice a day watering was common practice at both sites. It is suggested that long term policies should be made in the light of present findings to improve the productivity of rural production systems and facilitate the farmers to the maximum for improved goat production.